Elemental concentration of Late Cretaceous chalk and flint samples from the Hallembaye quarry, Belgium - Huygh, Jarno J C; Sinnesael, Matthias; Kaskes, Pim; Vellekoop, Johan; Van der Geest, Hannah; Jagt, John W M; Claeys, Philippe (PANGAEA, 2025)
This dataset contains the elemental concentration (expressed in weight per cent, either as element or as oxide), measured from 2019 to 2021 using a Bruker M4 Tornado micro-X-ray fluorescence (AMGC, VUB, Belgium), of Late Cretaceous chalk and flint samples that were sampled in 2019 at the Hallembaye quarry (Belgium). The data was collected to (i) investigate the imprint of astronomical forcing on the geochemical composition of chalk and to (ii) assess the geochemical composition of flint samples.
Keywords: Cretaceous; Cyclostratigraphy; micro-XRF; Milankovitch forcing; silica cycle